Un cuarto de siglo en la historia de la historia de las Matemáticas en Costa Rica (ING) - Ruiz, Ángel; Alfaro, Ana Lucía; Morales, Yuri (Uniciencia, 2003)
In the following pages, we will briefly describe the history of the History of Mathematics in Costa Rica, within the general evolution of the studies on the History of Science in this country. We will review the evolution of the Costa Rican Association for the History and Philosophy of Science, which was a very important platform for the development of this professional and academic field in the country. In Costa Rica, this association generate an authentic intellectual atmosphere and social respect favorable for the History of Science as a professional activity, something that was absent before. Later, we will analyze the main research groups dedicated to the History of Science and with more details to the History of Mathematics(organization, theoretical premises, themes and publications)